What Happens when Municipalities Run Corporations? Empirical Evidence from 290 Swedish Municipalities - Andreas Bergh; Gissur Ó. Erlingsson; Emanuel Wittberg (Research Institute of Industrial Economics (IFN), 2020)
Across the globe, local governments have increasingly begun to rely on municipally owned corporations (MOCs) to provide public services, mounting to what scholars describe as a burgeoning corporatization in local government. Some studies have described this development as a rational response to financial stress and contemporary austerity challenges, and emphasise the cost-efficiency of MOCs (the optimistic view). However, several scholars have identified problems associated MOCs relating to weak steering and supervision, lack of accountability, and heightened corruption risks (the sceptical view). Hitherto, no studies have tested these diametrically opposing expectations on the effects MOCs in the one and same analysis. This paper addresses the competing views by studying Sweden, a country with a dramatic growth in the number of MOCs since the 1970s. We examine the association between the number of MOCs, citizen satisfaction with local government, local tax rates and a survey-based corruption measure for all 290 Swedish municipalities. Ultimately questioning the 'optimistic view', the results indicate that municipalities that rely heavily on MOCs in service delivery have higher taxes, not more satisfied citizens, and are associated with higher corruption levels.
Keywords: D73; H79; 330; Municipally owned corporations; Corruption; Arms-length principle; Hybridorganizations; Quasi-privatization; New public management